Redes, capital humano e geografias da competitividade - João Luís Fernandes (Geografias, 2016)
In the scope of the 16th Cultural Week of the University of Coimbra (2014) with as reunited a set of investigators who, sharing the same scientific concerns, discuss the issue(s) around the subjects of networks, human capital and geography of competiveness.ALT_QUEBRA_LINHAIt resulted in a set of research works about contemporary territorial relations, between continuous spatial logics and discontinued, Euclidian and topological in which, apart from the old geographical issues, slower, it were considered also the faster and technological mediate and networks structured relations. The urgency of studies in this are results from the importance that networks have in the strategical settlement of locations, gaining interest the analysis of the relations of geographic proximity and continuity, as well as the discontinued relations, those that seek strategic affinity associations yet scarred by distant and fragmented geographical positions. The discussion is, thus, developed around the understanding of how the strategic affirmation of places, on one hand, and the promotion of human capital, on the other, depend, at the same time, on old and new geographies, on the relations of proximity, relations at a distance (in networks) and still of the resilience of populations in the sense of the capability to adapt and answer reactively and proactively.